2020
DOI: 10.1159/000506922
|View full text |Cite
|
Sign up to set email alerts
|

Association between Shoulder Range of Motion and Pain Catastrophizing Scale in Breast Cancer Patients after Surgery

Abstract: <b><i>Background:</i></b> Prolonged survival period as a result of early diagnosis and treatment in breast cancer has increased the importance of postoperative morbidities. The aim of the present study was to investigate the association of pain ca­tastrophizing with shoulder pain in patients with decreased shoulder range of motion in the postoperative period. <b><i>Patients and Methods:</i></b> The present study included 53 patients who underwent surgery due to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…However, we reported that the quality of life and satisfaction assessment was not affected apparently following OBSC regardless of the stage of the disease and the histopathological type. Also, we did not observe any differences among the physical and health functions of the quality of life scores regarding the surgical or operational approaches which was consistent with the literature (22). Larger and multicenter prospective studies are needed to fully reveal the relationship between other histopathological findings of breast tumors and quality of life scores in patients undergoing an OBSC.…”
Section: Discussionsupporting
confidence: 88%
“…However, we reported that the quality of life and satisfaction assessment was not affected apparently following OBSC regardless of the stage of the disease and the histopathological type. Also, we did not observe any differences among the physical and health functions of the quality of life scores regarding the surgical or operational approaches which was consistent with the literature (22). Larger and multicenter prospective studies are needed to fully reveal the relationship between other histopathological findings of breast tumors and quality of life scores in patients undergoing an OBSC.…”
Section: Discussionsupporting
confidence: 88%
“…The study adds to the growing body of evidence that pain catastrophizing is among the most important psychosocial factors contributing to the pain experience even among cancer survivors. [38][39][40] More than half of the sample had PCS scores above the therapeutic target of 10, and 56% had scores greater than 13. In other studies of noncancer pain, PCS scores greater than 13 to 16 are associated with a higher likelihood of an opioid prescription.…”
Section: Discussionmentioning
confidence: 99%
“…The modified radical mastectomy (MRM) and breast-conserving surgery (BCS) are standard treatment modalities in breast cancer surgery, while the sentinel lymph node biopsy (SLNB) or axillary lymph node dissection (ALND) could also be applied depending on the involvement of axillary lymph nodes. Although the incidence of breast cancer has been increasing, the mortality rates have decreased by developing anticancer therapies due to these developments in diagnostic and therapeutic facilities 12 . Increased efforts are being made to find a novel, effective, and safe anticancer treatment for human breast cancer 13,14 .…”
Section: Discussionmentioning
confidence: 99%